SOCIAL MEDIA AND USERS’ PARTICIPATION: IDENTIFYING THE ATTRIBUTES AND ITS IMPACT ON INFORMATION POLICY - Sayogo, Djoko Sigit (Universitas Muhammadiyah Malang)
Social media has grown remarkably and transform the communication mechanism. This recent advent of social media has escalated the hope of better and increase quality of users’ participation. This paper thus studies the impact of the determinants of social media usage on information policies, in particular information stewardship and usefulness. A combination of literary analysis, descriptive statistics of data from PEW Internet, and content analysis from interview were used as methodology to support the arguments. This study argues for five challenges related to the technological and users’ related usage of social media. These challenges are: a) clarity of users’ identity, b) conflict of information ownership & confidentiality, c) distinguishing public versus private information, d) definition of records & creation of meta data, and e) longevity of data & retention of records. Furthermore, this study proposes four critical factors that should be consider in the design and development of information policy governing the steward and use of information. These critical factors are: a) information credibility, integrity, and accuracy, b) security, privacy, and confidentiality of information, c) ensuring information access and availability, and d) data sharing and public-private partnership.